Penyidikan Terhadap Tindak Pidana Penyalahgunaan Izin Lokasi - Saragih, Julimaster; Marlina, Marlina; Zul, Muaz (ARBITER: Jurnal Ilmiah Magister Hukum, 2019)
Investigation This research has the aim of investigating and investigating a series of actions in terms of and in a way that will be stipulated in the law to find and gather evidence with evidence that makes minor violations occur and to determine suspects. This research is analytical descriptive with a normative juridical approach, using library materials (secondary material) or library law research that is broadly addressed to: research the principles of law, research on legal systematics, research on law synchronization, research on legal history and research against legal comparison. The results and discussion found that the location permit was issued by the Medan City Integrated Licensing Services Agency after obtaining the minutes of land technical considerations issued by the Medan City Land Office. The location permit is based on the Minister of Agrarian and Spatial Planning / Head of the National Land Agency Number 5 of 2015 concerning Location Permit. The form of abuse of the location permit holder is to release the land area not to the actual rights holder but to an unauthorized third party, namely the cultivating community, which subsequently the location permit holder controls and manages the land. (Law Number 51 PRP of 1960 Article 6 Concerning Prohibition of Use of Land Without a Right or Authorized Authority).